(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Premessa - 2. Definizione di Transumanesimo e i suoi principi – 3. Criticità e limiti del Transumanesimo - 4. Considerazioni conclusive. From homo erectus to homo Deus. Brief reflection on the new scientific-technological religions: Transhumanism ABSTRACT: The contribution aims to be a brief reflection on a new way of conceiving man and the future of humanity, no longer linked to physical-psychological decay but capable of becoming immortal. The Transhumanists, so called those who share this new ideology, are convinced that, thanks to technological development, by 2030 it will be possible to achieve objectives that today may seem surreal but which will give us, instead of man made of flesh, bones and passions, a cyborg able to think and live like a man but with much more developed and lasting potential.